Morfologia do intestino delgado de capivara - Hydrochoerus hydrochaeris (Linnaeus, 1766) - de Freitas, Noedi Leoni; de Paula, Moisés Calvo; Perri, Silvia Helena Venturoli [UNESP]; Ferraz, Rosa Helena dos Santos (My University, 2008)
The high potential for the exploitation of capybara requires information about its digestory morphophysiology, to improve nutritional handling. In the present study, gross anatomy, light microscopy and body and intestine lengths of 25 capybaras were evaluated. The minimum and maximum small intestine lengths for females and males were, respectively, 441 cm and 1734 cm, and 355 cm and 1123 cm. These values position the capybara between canine and swine intestinal lengths. The ratio between small intestine and body length was 12:1, without differences between sexes. There were no statistically significant differences between sexes for each part of small intestine. Correlation between length of each small intestine segment and body length was positive, and statistically significant only for the duodenum. The small intestine wall was formed by mucosa, submucosa, muscular and serosa. The mucosa presented intestinal and duodenal glands, of mucosal and serosal types, respectively. The mucosa muscular layer consisted of two distinct layers in the jejunum and ileum, and a thin and single layer in the duodenum. The submucosa, formed by moderate dense connective tissue, didn't show glands. The fiber bundles of the internal layer of muscular tunic were helicoidally arranged. The gross anatomy of the capybara small intestine was similar to canine and swine intestines. Microscopically, however, subtle differences can be identified in the submucosa and internal muscular tunics.
Morphology of capybara small intestine - Hydrochoerus hydrochaeris (Linnaeus, 1766)
Keywords: Gross anatomy; Length; Light microscopy; Rodent; Hydrochaeris hydrochaeris; Rodentia; Suidae